Pengaruh Word of Mouth terhadap Loyalitas melalui Kepuasan Pelanggan sebagai Variabel Intervening pada The Angkal Resto & Grill - Putri, Ni Ketut Wirayani; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Restaurant business quite promising and growing rapidly, requiring business people to be creative and innovate by paying attention to consumer desires. Loyal consumers can be customer return in building loyalty required word of mouth supported by customer satisfaction. This research to find the influence of WOM on customer satisfaction, know the influence of WOM and customer satisfaction in a parsial manner on customer loyalty and know the indirect influence of word of mouth on customer loyalty through customer satisfaction. A sample of 93 respondents. Use descriptive analysis and path analysis a sobell test. The results can include: word of mouth positively and significantly affected on customer satisfaction, word of mouth positively and significantly affected on customer loyalty, customer satisfaction positively and significantly to customer loyalty, word of mouth influence indirectly on customer loyalty through customer satisfaction. Advice for The Angkal Resto & Grill should always provide training to employees, supervise employees at work and try to make consumers feel satisfied.